THE EFFECT OF THE INTERNAL HEAVY ATOM ON SINGLET OXYGEN GENERATION IN THE PRESENCE OF PLASMONIC NANOPARTICLES - Ibrayev, N.Kh.; Menshova, E.P. (Eurasian Physical Technical Journal, 2025)
The heavy atom effect on singlet oxygen generation in the plasmon field of silver nanoparticles was investigated. The dyes rhodamine 123 and dibromrhodamine 123 in polyvinyl butyral films were used as sensibilisers. The dye films were deposited by spin-coating onto silver island films synthesised on the quartz surface. The results showed that the presence of bromine atom in the dye molecules increased the singlet oxygen generation efficiency. The calculated Stern-Follmer constants demonstrate the enhancement of molecular oxygen quenching of triplet states of dibromorhodamine 123 dye molecules in the presence of Ag nanoparticles.